Step-by-step explanation:
Plug x in :
-8(7-3) = -32
Distribute :
-56 - (-24) = -32
Subtract :
-32 = -32
Answer:
After simplifying, the exponent of x is 33 and the exponent of y is 0
Step-by-step explanation:
For us to simplify, we bring the x base together and the y base together
Recall from the law of indices;
x^a/x^b = x^(a-b)
and x^a * x^b = x^(a + b)
We shall be applying these here
Let us bring the x terms together
we have these as;
x^8/x^14 * 1/x^-39 = x^( 8 - 14 -(-39))
= x^(8 + 39-14) = x^33
for y, we have it that;
y^-26/y^-5 * 1/y^-21
= y^(-26 -(-5) - (-21)
= y^-26 + 5 + 21 = y^0
The blank is -8 because -6 +-8=-14+-3=-17.